The Anatomical Distribution of Fluorescence Caused by Pseudomonads in Anguispira Kochi (Pfeiffer) - Roger L. Yates; Hugh C. Rawls (Hello World!, 1972)
During a study of chromatograms of tissues of various species of land snails, certain chromatograms were observed to exhibit a vivid, blue fluorescence when subjected to ultraviolet illumination. Further investigation indicated that this fluorescence was characteristic of certain endodontid species and suggested that it would be found to occur in all members of the family (Rawls and Yates, 1971). A subsequent study reported the same kind of fluorescence in the mucus of Mesodon clausus, a polygyrid (Rawls and Baum, 1971). Fluorescence of a different kind has been reported in the mucus of Helix aspersa Muller, an helicid (Turchini, 1926; Fischer and Saddy, 1949), and in the epiphragms of certain other snails (Fischer, 1956).